1996
DOI: 10.1177/00220345960750091001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Efficacy of Amorphous Calcium Phosphate/Methacrylate Composites in Remineralizing Caries-like Lesions Artificially Produced in Bovine Enamel

Abstract: Recent studies show that methacrylate-based composites with amorphous calcium phosphate (ACP) as a filler can release supersaturating levels of calcium and phosphate ions in proportions favorable for apatite formation. These findings suggest that such composites could be effectively used as coatings for remineralizing teeth damaged by tooth decay. To examine this hypothesis, we tested composites in vitro for their efficacy to remineralize artificially formed caries-like lesions in extracted bovine incisors. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 20 publications
4
128
0
9
Order By: Relevance
“…Therefore, for stress-bearing restorations, it would be desirable to use a composite with a DCPA:whisker ratio near 1:1 using unsilanized DCPA nano-particles, which produced a Ca concentration of 0.35 mmol/L and PO 4 of 0.99 mmol/L (at 56 d). These concentrations matched or exceeded the reported Ca and PO 4 concentrations measured using a similar method for previous calcium phosphate composites known to remineralize enamel and dentin lesions in vitro [18][19][20][21]. For example, amorphous calcium phosphate (ACP) composites yielded a Ca concentration of 0.3 mmol/L to 1.0 mmol/L, and a PO 4 concentration of 0.2 mmol/L to 0.7 mmol/L (Figs.…”
Section: Effect Of Dcpa Particle Silanizationsupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, for stress-bearing restorations, it would be desirable to use a composite with a DCPA:whisker ratio near 1:1 using unsilanized DCPA nano-particles, which produced a Ca concentration of 0.35 mmol/L and PO 4 of 0.99 mmol/L (at 56 d). These concentrations matched or exceeded the reported Ca and PO 4 concentrations measured using a similar method for previous calcium phosphate composites known to remineralize enamel and dentin lesions in vitro [18][19][20][21]. For example, amorphous calcium phosphate (ACP) composites yielded a Ca concentration of 0.3 mmol/L to 1.0 mmol/L, and a PO 4 concentration of 0.2 mmol/L to 0.7 mmol/L (Figs.…”
Section: Effect Of Dcpa Particle Silanizationsupporting
confidence: 75%
“…Previous studies [18][19][20][21] showed that when the Ca and PO 4 ions were released from the composite restoration, they reprecipitated to form hydroxyapatite outside the composite and inside the tooth lesions, significantly increasing the mineral content of the lesion. The fact that the Ca and PO 4 concentrations from the DCPA-whisker composite matched or exceeded those of the previous calcium phosphate composites suggests that the DCPA-whisker composite may also be an effective remineralizer.…”
Section: Effect Of Synergistic Use Of Nano-releasing Fillers/reinforcmentioning
confidence: 99%
See 1 more Smart Citation
“…ACP-containing bioactive materials stimulate mineral growth by increasing calcium and phosphate concentrations within the lesion, especially in the acidic oral environment, to levels that exceed those existing in ambient oral fluids. This shifts the thermodynamic driving force toward apatite formation 11,12) . ACP can also sustain these supersaturation conditions, which are favorable for apatite formation, over extended periods of time 11,12) .…”
Section: Introductionmentioning
confidence: 99%
“…ACP-filled composite resins have been shown to recover 71% of the lost mineral content of decalcified teeth. 4 One ACP-containing adhesive, Aegis Ortho (The Bosworth Co, Skokie, Ill), has been marketed for use as a lightcured orthodontic adhesive with similar properties to previously used resins. The premise behind this product is that during a carious attack around orthodontic brackets, at or below pH 5.8, hydroxyapatite (HAP) is leached from the enamel surface.…”
Section: Introductionmentioning
confidence: 99%